Billy - French, Albert (New York : Penguin Books, 1995)
Set in the 1930s in a small Mississippi town the story is about racism and about a ten-year-old boy who is convicted of and executed for murdering a white girl.
Wilson's Fiction.
Young Adult
Keywords: Racism -- Mississippi -- Fiction; Racism -- Mississippi -- Fiction; Mississippi -- Fiction; Mississippi -- Fiction